Processos de construção da identidade de mentoras iniciantes - Silva, Jéssica Francine Ferreira da (Universidade Federal de São Carlos, 2020)
This present research project comes from the work performed in an intervention research called “Teacher Professional Development of experienced teachers and beginners: Hybrid Mentoring Program (HMP)”, financed by FAPESP/São Paulo/Brazil, coordinated by teachers from Teacher Formation and other Educational Agents line (area), from São Carlos Federal University. The objective of this research’s project was to understand the process of the construction of the identity of beginner mentors from their formation paths, professional and HMP’s participation. For that, we had specific objectives to identify elements from their personal paths and professionals that influentiate the development of their mentors identity; investigate their comprehension about mentor and their mentors roles; list and characterize the stress and ways dealing with mentors exercise role. This research, within qualitative nature, had four mentoring teachers as collaborative participants from HMP; one professor from Childhood Education, two professors from Secundary Education and one professor from Young and Adults Education. The proposal of this research is to investigate the identity construction of these mentors, members of HMP, from the comprehensive-interpretive analysis from written narratives performed from them in the “Virtual Learning Environment” and the oral narratives, more specific semi structured interviews, observing their formation trajectory, professional, as well the HMP participation. The data demonstrated that the identity construction process of the mentors that involved their personal and professional paths, had included childhood aspects (experiences from family and in different contexts), professional formation, teacher practice and professional actuation, as well their motivations and ideology built in these periods; theirs comprehensions about mentoring and their role involved in such manner intersubjective theirs perception, learning, building, actions and decision making in theirs mentoring practice and formation; and theirs stress and ways of confrontation lived in the mentors work involved their difficulties, challenges, anguish, demotivation in the process of mentoring the beginners teachers and the ways they deal with this process, overcome or, still, outlined these problems to keep accomplishing their work as mentors. Beyond that, considering these mentors are beginners in this new role, we realize that during their identity construction process they passed through a phase of induction similar as a beginner teacher and built a new identity from their teacher identity, modifying their knowledge base due the exercise of the new role demands. This process revealed the necessity of acquisition of new experiences, abilities and self knowledge, as well it was not free of conflicts and stress. That said, the data also emphasizes and reinforce the importance of induction programs, moreover the advisory formation of experienced teachers to auxiliate beginners, evidencing the necessity of a specific formation of mentoring teachers so that they understand their roles and specificities of this function. In this way, it is essential the implementation of Public Politics in induction programs and/or mentoring that also accomplish the experienced teachers needs, considering their role, development time e work conditions.
Identity construction processes of beginning mentors
Keywords: Programa híbrido de mentoria; Identidade profissional; Professoras mentoras; Hybrid mentoring program; Professional identity; Mentoring teachers; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO